O corpo em cena na Educação de Jovens e Adultos: a mobilização para a aprendizagem na EJA por meio dos significados expressos pela corporeidade de mulheres adultas - Luiz Olavo Fonseca Ferreira (2013)
This work, through dialogue between education and corporeality, investigated the behavior of the adult students EJA during educational activities. For that, I present a literature review on the body and about the conception of corporeality. Then perform a discussion of the concepts of the relationship to knowledge and mobilization, as well as addressing gender discussions, focusing on womanhood and specificity of educating fellow worker of Education of Youth and Adults. Research subjects were five students of EJA, aged 30 to 40 years, a municipal school in Belo Horizonte. I used the methodology of qualitative research. Data were collected through observation, semi-structured interviews and theater games and are presented, divided into conduct observed during the teaching activities and the meanings attributed by educandas the body. They were organized, at first, considering the spatial distribution, bodily behaviors, the interaction of the students with the teacher and interaction with other students. Then the results were analyzed from motherhood, family, housework, work outside the home and urban space. It was evident the difficulty of building an "approximate body experience in adult education," pointing to the need for more research on the subject. Realized the existence of female bodies disciplined, but that, through this same embodiment, the students demonstrated , from their behavior, they are mobilized, and also "demobilized" to the process of teaching and learning. Seeking to respond to what motivated me to investigate the corporeality and relationship with knowledge, I believe that there are different ways to mobilize for learning and adult women students of Youth and Adults, show, in most cases, by its corporeality that provision or not to attend a class.